Size effects on the magnetoelectric response on PVDF/Vitrovac 4040 laminate composites - Silva, M. P. (2015)
Tri-layered and bi-layered magnetoelectric (ME) flexible composite structures of varying geometries and sizes consisting on magnetostrictive Vitrovac and piezoelectric poly(vinylidene fluoride) (PVDF) layers were fabricated by direct bonding. From the ME measurements it was determined that tri-layered composites structures (magnetostrictive-piezoelectric-magnetostrictive type), show a higher ME response (75 V.cm-1.Oe-1) than the bi-layer structure (66 V.cm 1.Oe-1). The ME voltage coefficient decreased with increasing longitudinal size aspect ratio between PVDF and Vitrovac layers (from 1.1 to 4.3), being observed a maximum ME voltage coefficient of 66 V.cm-1.Oe-1. It was also observed that the composite with the lowest transversal aspect ratio between PVDF and Vitrovac layers resulted in better ME performance than the structures with higher transversal size aspect ratios. It was further determined an intimate relation between the Vitrovac PVDF Area Area ratio and the ME response of the composites. When such ratio values approach 1, the ME response is the largest. Additionally the ME output value and magnetic field response was controlled by changing the number of Vitrovac layers, which allows the development of magnetic sensors and energy harvesting devices.